تأثير نقص العناصر النادرة في التركيب الكيميائي لأوراق وبذور القطن باستخدام المزارع الرملية (Latakia University Journal -Biological Sciences Series, 2019)
نفذ البحث في مزرعة كلية الزراعة، لدراسة تأثير نقص العناصر النادرة في محتوى أوراق القطن من N.P.K في مرحلة النضج ونسبة الزيت والبروتين في لب البذور%، ثم زراعة بذور الصنف حلب 133 في أصص بلاستيكية معبأة بالرمل، استخدمت 14 معاملة سمادية. بينت الدراسة النتائج الآتية: 1 ـ تفوقت معاملة الشاهد (محلول هوجلند) في نسبة الزيت والبروتين، ونسبة N.P.K في الأوراق بالمقارنة مع جميع المعاملات المدروسة. 2 ـ انخفضت معنوياً متوسطات نسبة الآزوت والفوسفور والبوتاسيوم في المعاملة (T6) معاملة هوجلند عدا البورون ومعاملة هوجلند عدا الزنك (T5) قياساً بالشاهد وباقي المعاملات. 3 ـ انخفضت معنوياً نسبة الزيت والبروتين عند جميع المعاملات قياساً بالشاهد وبلغ أكبر انخفاض عند معاملة هوجلند عدا الزنك (T5)، ثم عدا البورون (T6). This study was conducted in the faculty of agriculture farm. Cotton seeds of Aleppo 1-33 variety were planted in plastic pots filled with sands, and 14 fertilizing equations were used to study the effect trace element deficiency in the content of cotton leaves from N.P.K in mature stage, and the percentage of oil and proteins in seeds. This study showed the following results: 1-                      Hoagland treatment (control) was the best in the percentage of oil, proteins, and N.P.K in leafs in comparison with all other treatments. 2-                      The means of nitrogen, phosphor, and potassium in Hoagland treatment without boron (T6), and Hoagland with zinc (T5) were reduced in comparison with the control and other treatments. 3-                      The percentage of oil and protins in all treatments were significantly reduced in compassion with control treatment. The highest reduction was in treatment without zinc (T5) and Hoagland without boron (T6).